Chinese Herbal Medicine Used With or Without Conventional Western Therapy for COVID-19: An Evidence Review of Clinical Studies - Liang, Shi-Bing; Zhang, Ying-Ying; Shen, Chen; Liang, Chang-Hao; Lai, Bao-Yong; Dai, Ning; Li, Yu-Qi; Tian, Zi-Yu; Zhang, Xiao-Wen; Jiang, Yue; Xiong, Min; Zhang, Ya-Peng; et al. (Frontiers in Pharmacology, 2021)
Objective To present the evidence of the effectiveness and safety of Chinese herbal medicine (CHM) used with or without conventional western therapy on COVID-19. Methods Clinical studies on effectiveness and safety of CHM for COVID-19 were included. We summarized general characteristics of included studies, evaluated methodological quality of randomized controlled trials (RCTs) using the Cochrane risk of bias tool, analyzed the use of CHM, used Revman 5.4 software to present the risk ratio (RR) or mean difference (MD) with their 95% confidence interval (CI) to estimate the effectiveness and safety of CHM. Results A total of 58 clinical studies were identified including RCTs (17.24%, 10), non-randomized controlled trials (1.72%, 1), retrospective studies with a control group (18.97%, 11), case-series (20.69%, 12) and case-reports (41.38%, 24). No high methodological quality RCTs were identified. The most frequently tested Chinese patent medicine, Chinese herbal medicine injection or prescribed herbal decoction were: Lianhua Qingwen granule/capsule, Xuebijing injection and Maxing Shigan Tang. In terms of aggravation rate, pooled analyses showed that there had statistical differences between the intervention group and the comparator group (RR 0.46, 95% CI 0.30 to 0.68, 7 RCTs; RR 0.37, 95% CI 0.22 to 0.64, 4 retrospective studies with control group), that is, CHM plus conventional western therapy appeared better than conventional western therapy in reducing aggravation rate. In addition, compared with conventional western therapy, CHM plus conventional western therapy had potential advantages in increasing the resolution rate and shortening the duration of fever, cough and fatigue, improving the negative conversion rate of nucleic acid test, and increasing the number of patients with inflammatory disappearance or shortening the time from receiving treatment to beginning of inflammation disappearance. For adverse events, pooled data showed that there was no statistical difference between the CHM and the control groups. Conclusion Current low certainty evidence suggests that there maybe a tendency that CHM plus conventional western therapy is superior to conventional western therapy alone. The use of CHM did not increase the risk of adverse events.